Epiphytic Microorganisms Associated with Banana Phyllosphere with Potential Antagonism to Black Sigatoka (Pseudocercospora fijiensis) in Los Ríos, Ecuador - Tigselema Zambrano, Solanyi Marley; Villalba Puga, Aracelly Mabel; Ochoa Ramos, Jim Raphael; Lara Hidalgo, Galo Efraín; López, Diana Aracelly (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
Black Sigatoka (Pseudocercospora fijiensis) is the most important leaf spot disease of bananas worldwide, particularly affecting Cavendish banana, the most exported variety. Additionally, this pathogen has developed resistance to some effective fungicides, making its management increasingly difficult. Epiphytic microorganisms with potential antagonism to P. fijiensis were identified in conventional banana farms in the province of Los Ríos. Sampling areas were determined through zoning processes and selecting the cantons of Mocache, Valencia, Baba and Pueblo Viejo. Leaf tissue samples were collected from three farms per zone. Microorganisms were isolated and morphologically and molecularly characterised in nine farms in the cantons of Valencia (63 bacteria), Baba (39 bacteria), Pueblo Viejo (8 bacteria) and 8 genera of fungi including 15 species. The isolated bacteria presented macroscopic and microscopic characteristics with different shapes, elevations, edges, consistencies and pigmentations. Taxonomically, they belonged to the genera Bacillus and Cocos, 81% Gram-negative and 19% Gram-positive. The analysis conducted for sampling-site selection allowed the identification of different microbial behaviours. Highlights: Biological control offers a viable strategy to reduce reliance on agrochemicals in agricultural practices. The isolation and characterization of microorganisms are essential for researching and developing biological solutions applicable to banana cultivation. The data obtained provide crucial insights for formulating and developing bioinoculants.